A Study of Toddlers’ Humor Linguistic Mind - Dian Eka Chandra Wardhana; Gita Mutiara Hati (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
Humor for a child can improve his intelligence and smooth his feeling and as a result, he has a strong mental endurance which affects physical stamina. Humor is considered as a language play in several aspects of language structure and function. Therefore, this study explains the linguistic view which explicitly and implicitly used by the speaker when telling humor. This is a qualitative study with ethnography of communication and pragmatic approach. The data are in the form of toddlers’ speech when they are communicating using humor which is represented while they are playing with their families and playmates. The data was then documented in the form of descriptive and reflective recording and field notes. The findings of this study show that humor is represented through language play such as pragmatics, syntax, morphology, phonology, and semantics in language mind with implicit meaning. Therefore theories of ambiguity play a role in linguistic mind. However, this study only focuses on the discussion of humor in toddlers’ linguistic mind which is represented in their speech act.